Analisis Inovasi Produk UMKM Agribisnis (Tanaman Hias)dengan Pendekatan Ekonomi Islam terhadap Peningkatan Daya Saing Lokal (Studi Kasus Kota Bandung) - Salam, Mochamad Fadlani; Siregar, Muhammad Zaki Mulia; Rahayu, Sinta Sri; Fadhillah, Ilham; Nurfauziah, Muhammad Adistya (Yayasan Sagita Akademia Maju, 2025)
This study examines product innovation in ornamental plant agribusiness MSMEs in Bandung City using an Islamic economics approach to enhance local competitiveness. The method used is qualitative descriptive, combining in-depth interviews with three MSMEs and a review of previous research literature. Findings indicate that integrating the principles of honesty, fairness, and trustworthiness into every stage of innovation, from the use of decorated used pots to the development of